If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + 2) = x + 2(x + -1) Reorder the terms: -4(2 + 3x) = x + 2(x + -1) (2 * -4 + 3x * -4) = x + 2(x + -1) (-8 + -12x) = x + 2(x + -1) Reorder the terms: -8 + -12x = x + 2(-1 + x) -8 + -12x = x + (-1 * 2 + x * 2) -8 + -12x = x + (-2 + 2x) Reorder the terms: -8 + -12x = -2 + x + 2x Combine like terms: x + 2x = 3x -8 + -12x = -2 + 3x Solving -8 + -12x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + -12x + -3x = -2 + 3x + -3x Combine like terms: -12x + -3x = -15x -8 + -15x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + -15x = -2 + 0 -8 + -15x = -2 Add '8' to each side of the equation. -8 + 8 + -15x = -2 + 8 Combine like terms: -8 + 8 = 0 0 + -15x = -2 + 8 -15x = -2 + 8 Combine like terms: -2 + 8 = 6 -15x = 6 Divide each side by '-15'. x = -0.4 Simplifying x = -0.4
| 8(5x-6)=152 | | 2x=8+y | | -18+12x=10x+14 | | -8=-(4)+4 | | =x^4-4x^3+3x^2-4x+2 | | 11.95x+4.95=64.70 | | 7=m/2 | | 11-8x=75-36x | | 8p^2-2p+15=0 | | -2x+y=-8 | | 4n-1=-29 | | 0.5y=-6 | | 7-3(p+5)=27 | | 56x^3/(42x^2) | | 3(6-b)-33=27b-5(3+6b) | | 58+11x=6x+92 | | Mx+mx=p | | 3(4x+3)-8=13 | | -0.4x+20=-16 | | a=-10+2b | | 3x-4=4(x+3) | | 3.5x+8=x | | m-6m=8 | | 3.5x=8 | | 7u-w=u-6w | | -2/22x7/41 | | 16/10+9/2-21/4 | | 48x^2+22x-25=0 | | -305=5(8n-5) | | (5-3x)-2(-4x+6)= | | 15-x+6y-2= | | 3x-100=6x+26 |